Histopathological study of adrenocortical masses with special references to Weiss score, Ki-67 index and p53 status - Gautam Mukherjee; Chhanda Datta; Uttara Chatterjee; Moumita Sengupta; Gaurav Chatterjee; Malay Bera; Subhankar Chowdhury (Wolters Kluwer Medknow Publications, 2015)
Background: Adrenal mass present with wide morphological spectrum and clinical manifestation, which can give rise to diagnostic confusion. Proper categorization is essential for individualized treatment. Aim and Objective: (1) Application of Weiss criteria to differentiate between benign and malignant adrenocortical neoplasm (2) co-relation of Ki-67 and p53 expression with the Weiss score. Materials and Methods: A prospective, observational study was conducted in the Department of Pathology in collaboration with department of Endocrinology and Urology of a tertiary care hospital including 19 patients presented with clinically symptomatic or radiologically detected adrenocortical mass. Tissue for histopathological study was obtained in the form of the postoperative material. Histopathological categorization was done, and Weiss score was calculated in all tumors. Ki-67 and p53 immunohistochemistry were performed. Result: A total 19 cases of adrenal mass lesions were included. Cushing syndrome was the presenting symptoms in 26.3% adrenocortical masses. All patients with tumors with Weiss's score <3 (Group 1) were alive after 24 months of follow-up compared to 20% of those with Weiss's score >3 (Group 2). Statistically significance difference was noted in average weights and size of the tumors. Distribution of Ki-67 and p53 expression between Group 1 and Group 2 were compared and found statistically highly significant with Fisher's two-tailed P < 0.001. Conclusion: The combination of the meticulous evaluation of clinical, morphological and immunohistochemical profile helps in proper categorization of adrenocortical mass.